2015
DOI: 10.1016/j.sbspro.2015.04.118
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Attitudes Towards Foreign Language Learning: Pursuit of Relevance and Implications

Abstract: Research into second language acquisition (SLA) has confirmed the inadequacy of Intelligent Quotient (IQ) in accounting for success in second or foreign language learning (L2). Many studies conducted on the role of intelligence in successful learning, especially in English as a foreign language (EFL) classroom settings in different contexts, have shown that there are other areas of intelligence that contribute to quality learning. Thus, the present study investigated the possible relationship between perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Willingness to communicate had a positive correlation with EI and a negative correlation with L2 anxiety, based on the data from their 88 students. Oz, Demirezen, & Pourfeiz (2015) found that their 159 Turkish university students majoring in EFL displayed high levels of overall EI and a satisfactory level of attitudes towards L2 learning. The perception of emotion subdomain was the strongest predictor of cognitive and behavioral/personality while the utilization subdomain was the strongest predictor of affective/evaluative components of attitudes towards L2 learning.…”
Section: Emotional Intelligence In Slamentioning
confidence: 95%
“…Willingness to communicate had a positive correlation with EI and a negative correlation with L2 anxiety, based on the data from their 88 students. Oz, Demirezen, & Pourfeiz (2015) found that their 159 Turkish university students majoring in EFL displayed high levels of overall EI and a satisfactory level of attitudes towards L2 learning. The perception of emotion subdomain was the strongest predictor of cognitive and behavioral/personality while the utilization subdomain was the strongest predictor of affective/evaluative components of attitudes towards L2 learning.…”
Section: Emotional Intelligence In Slamentioning
confidence: 95%
“…In the study of Engelberg, emotional intelligence has been proposed as a general ability for emotional and social compromise. Emotional compromise can include good mental health, satisfaction with personal life and coordination between feelings, activities and thoughts 28 . Gellman believes that emotional intelligence is another aspect of intelligence that plays an important role in achieving people's ability to succeed in different aspects of life, more than cognitive intelligence.…”
Section: Modabber Arasteh and Seyedeh Asrin Seyedoshohadaeimentioning
confidence: 99%
“…Similarly, in a study with 510 Chinese EFL students, Shao, Yu and Ji (2013) found a significant negative correlation (r = -0.681, p< 0.01) between students' EI and foreign language anxiety. Oz, Demirezen, and Pourfeiz (2015) looked at the relationship between perceptions of EI and attitudes towards foreign language learning among 159 Turkish university EFL learners. Their findings showed that EI and attitudes towards foreign language learning were positively correlated, and that self-awareness and self-regulation of emotions were the strongest predictors of overall EI.…”
Section: Emotional and Social Intelligence In Language Teachingmentioning
confidence: 99%